Maths Sparks engagement programme: investigating the impact on under-privileged pupils' attitudes towards mathematics. (15th August 2020) - Ni Shuilleabhain, Aoibhinn; Cronin, Anthony; Prendergast, Mark
Abstract: In this paper we explore the attitudes of under-privileged secondary school pupils in Ireland towards mathematics and investigate the impact of attending a 4-week engagement programme on these attitudes. The pupils involved in this research attended schools recognized by the Department of Education & Skills as socio-economically deprived. Pupils attending these schools, known as Delivering Equality of Opportunity in Schools (DEIS), are 40% less likely than their counterparts in non-DEIS schools to pursue mathematics at a higher level in state examinations (Smyth, E., Mccoy, S. & Kingston, G., 2015, Learning From the Evaluation of DEIS . Dublin: Economic and Social Research Institute). However, little research has reported on these pupils' experiences of and attitudes towards mathematics at senior secondary level. An engagement programme entitled 'Maths Sparks' was purposefully designed for secondary pupils from DEIS schools, with the aim of positively influencing their attitudes towards and confidence in mathematics. The programme consisted of weekly out-of-school workshops exploring extra-curricular mathematics topics, designed and delivered by undergraduate mathematics students. Questionnaires were utilized to evaluate pupils' attitudes towards mathematics before and after their participation in the programme. Despite its relatively short time frame, qualitative and quantitative analysis suggests an increase in participating pupils' attitudes towards, enjoyment of and self-confidence in mathematics due to their participation in the programme. Findings also suggest that while these pupils liked the subject of mathematics, their experience of learning the subject in school was not always positive and was sometimes hindered by the absence of higher-level mathematics as an option in school. The high-stakes examination content and teachers' beliefs in the ability of their students also sometimes negatively impacted learners' intentions to pursue mathematics at a higher level. Findings suggest that longitudinal mathematics engagement programmes, which focus on problem solving, involve extra-curricular mathematical concepts and are presented by undergraduate mathematics students, may provide a valuable way of positively impacting pupils' intentions to pursue the subject.